Ecología trófica del sábalo Megalops atlanticus (Pisces: MegaIopidae) en el área de Ciénaga Grande de Santa Marta, Caribe colombiano - Cataño, Santiago (1994)
Stomach content composition of 582 specimens (120-530 mm in fork 1ength) of the tarpon (Megalops atlanticus Valenciennes) collected between February and December 1990 was studied using gravimetric and frequency methods in the Ciénaga Grande de Santa Marta area, an estuarine-de1taic system in the Caribbean coast of Colombia. Eleven food categories were quantified, including gastropods, shrimps, insects, fishes and plant remains. Diet is composed basically of two fish groups: mullet juveniles (Mugil spp., probab1y M. incilis in a great proportion) and mollies (probably PoeciUa cf. gilli). The former domínates the diet from March to July, when massive inmigrations of mullet juveniles occur from the sea. The mollies, which seem to be resident, became abundant in tarpon stomachs only between September and February, when young mullets are scarce in the area. Larger tarpons are more piscivorous and less insectivorous. lnsects are a1so more abundant in the food of tarpoon collected in swamps (where diet is a180 more diverse), than in river mouths where environmental changes are stronger and more frequent